Enjeux d’inégalités associées aux solutions d’adaptation aux changements climatiques : qu'est-ce qu'on en sait ? - Nathalie Bleau; Emily Després (VertigO)
In Quebec, in response to the impacts of climate change and its consequences, many public, private and community organizations are implementing adaptation solutions to strengthen the resilience of populations to climate change. Recent studies are now linking adaptation options to the potential generation or exacerbation of inequalities. The issue of inequalities in climate change adaptation solutions (CCA) was increasingly mentioned by Ouranos and its partners as an issue that needed to be documented, all the more so when the aim is to accelerate adaptation. It was therefore pertinent, in order to properly support those involved in adaptation, to establish a base, to identify key concepts that enable us to explore the mechanisms that have helped to respond to similar issues, to evaluate the analysis methods used, and to highlight the strengths, weaknesses and controversies of established ideas in the field. Some mechanisms exist to identify these inequality issues. Some authors propose alternative adaptation solutions to climate change that aim to reduce such inequalities. Despite the progress made in recent years, several aspects concerning inequalities generated or potentially generated by adaptation solutions require further exploration: Some solutions and sectors of activity lack sufficient documentation; certain populations and regions are less studied than others; and certain processes, such as methods for monitoring and evaluating adaptation solutions, would benefit from additional research focus.